STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN PROFESIONALISME GURU TK - Huriah, Huriah; Rayhanah, Siti; Erawati, Erni; Suriansyah, Suriansyah; Purwanti, Ratna (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT Improving the quality of Early Childhood Education is highly dependent on the professional capacity of teachers, yet the development of this competency is often not systematically planned. This study aims to analyze the principal's leadership strategy in developing professionalism and empowering teachers at Azzahra Kandangan Kindergarten. Using a qualitative approach with a case study method, the research stages included data collection through in-depth interviews, participatory observation, and documentation studies, whose validity was tested through source triangulation. Data were analyzed using an interactive model that encompasses reduction, presentation, and accurate conclusion drawing. The results revealed that the principal implemented humanistic participatory leadership through routine academic supervision and providing equitable learning opportunities for all teaching staff. The findings indicated active collaboration within the internal learning community and teacher involvement in strategic curriculum planning such as the development of RPPH, semester programs, and annual programs. This strategy significantly increased teacher work motivation, self-confidence, and independence in aspects of pedagogical competence and professional personality. The main conclusion confirms that a non-authoritarian leadership style based on collective empowerment can create a supportive school climate that is essential for sustainable professional growth. This research recommendation points to the need for a more integrated teacher development structure to ensure the quality of early childhood education services remains superior and adaptive to the dynamics of modern developments.   ABSTRAK Peningkatan mutu Pendidikan Anak Usia Dini sangat bergantung pada kapasitas profesional guru, namun sering kali pengembangan kompetensi ini belum terencana secara sistematis. Penelitian ini bertujuan menganalisis strategi kepemimpinan kepala sekolah dalam mengembangkan profesionalisme serta memberdayakan guru di TK Azzahra Kandangan. Menggunakan pendekatan kualitatif dengan metode studi kasus, tahapan penelitian meliputi pengumpulan data melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi yang diuji keabsahannya melalui triangulasi sumber. Data dianalisis menggunakan model interaktif yang mencakup reduksi, penyajian, hingga penarikan simpulan secara akurat. Hasil penelitian mengungkap bahwa kepala sekolah menerapkan kepemimpinan partisipatif yang humanis melalui supervisi akademik rutin dan pemberian kesempatan belajar yang adil bagi seluruh staf pendidik. Temuan menunjukkan adanya kolaborasi aktif dalam komunitas belajar internal serta pelibatan guru dalam perencanaan kurikulum strategis seperti penyusunan RPPH, program semester, dan program tahunan. Strategi ini secara nyata meningkatkan motivasi kerja, kepercayaan diri, serta kemandirian guru dalam aspek kompetensi pedagogik maupun kepribadian profesional. Simpulan utama menegaskan bahwa gaya kepemimpinan yang tidak otoriter dan berbasis pemberdayaan kolektif mampu menciptakan iklim sekolah suportif yang esensial bagi pertumbuhan profesional berkelanjutan. Rekomendasi penelitian ini mengarah pada perlunya struktur pengembangan guru yang lebih terintegrasi guna memastikan kualitas layanan pendidikan anak usia dini tetap unggul dan adaptif terhadap dinamika perkembangan zaman.